More than just reacting: a behavior sequence analysis of victim-offender interactions during violent crime - Fuller, Georgina (Journal of interpersonal violence, 2025)
The victim–offender interaction is an important part of violent incidents. However, very little research has examined how the actions of both parties’ shape and influence the behavior of the other. While the offender’s behavior and role in shaping the nature of the incident has received a large amount of attention, the corresponding influence of victim behavior is less understood. This study uses behavior sequence analysis to map victim–offender interactions during 149 cases of domestic violence, sexual assault, and physical assault (collectively referred to as physically assaultive crime) to understand how victim behavior shapes, and is shaped by, the offender during violent crime. By using the interpersonal circumplex—a probabilistic model of human behavior during social interactions—and its associated principle of complementarity to frame the analysis, the results emphasized the reciprocal influence a victim has on the offender. Results showed that while this dynamic mostly reflected other, non-violent, social interactions, key deviations in how victims responded to offenders may indicate that victims are not simply reacting to the offender but seeking their own ways to influence how the crime unfolds. These findings not only provide new insight into how physically assaultive crime unfolds but also have important implications for how we conceptualize a victim’s role and agency during violence.